7-TH Winter School on Molecular and Quantum Acoustics and Sonochemistry, Ustronie – Brzegi, February 1978 - M. M. DOBRZAŃSKI (Archives of Acoustics)
The seventh Winter School on Molecular and Quantum Acoustics and Sonochemistry, organized by the Institute of Physics of Silesian Technical University in Gliwice and the Molecular and Quantum Physics Section of the Polish Acoustical Society with the participation of the coordinator of the interdisciplinary problem MR.I.24, was held on February 21-26, 1978, at Ustronie-Brzegi. Dr. Stanislaw Szyma (Institute of Physics, Silesian Technical University in Gliwice) was the chairman of the Organizing Committee. The School was attended by some 60 participants, i.e. twice as many as last year. They came from over 10 national scientific centres, sponsored by the Polish Academy of Sciences, the Ministry of Higher Education and Technology and by other ministries. Six sessions were held at which 37 lectures and reports were delivered giving a general description of investigations carried out in Poland in the field of quantum acoustics, acoustoelectronics and acoustooptics, ultrasound spectroscopy and sonochemistry and providing the information on the current trends in the world science. In comparison with the last year there could be observed a growing interest in the problems of acoustooptics and quantum acoustics.